AND THE JOURNEY CONTINUES: EXPLORING THE PROFESSIONAL REPLACEMENT OF HIGH ACHIVEMENT EX-ATHLETES - Maciel, Luiz Henrique Rezende (2015)
The aim of this study was to understand the career transition of athletes, considering the completion of his or her career as a professional. For this it was selected a group of six former athletes, in individual sports, which during their sports career were members of the national teams of winning titles such as the South American, Pan American and / or Olympic. The research consisted of conducting semi-structured interviews with participants, from which we sought to apprehend aspects of the construction of the sports career from the first contact with sport, as well as the existence of a career after acting as professional athletes and their consequent construction considering transitions experienced throughout the process. This was an interpretative approach, thus opting for the interpretative paradigm. The nature of this research was qualitative. For data analysis we proceeded with content analysis from the proposition of an analytical framework composed of elements related to career and sport career concepts. The narratives were analyzed from three fixed categories: Career Sports, Career Transitions, and The Construction of a "New" Career. It was observed that the sports career started and ended early, due to age. Great importance was attributed to the coaches when regarding guidance and planning a sports career as well as afterwards. The influence of family it was considered strong, even if not always positive. The choice for a new career was, in most cases, influenced by the sports practice and is considered to be responsible for the development of physical, cognitive and especially emotional for effective coping and career development after being an athlete.